Evolution of EFTA in Differentiated Integration within Europe - V. V. Zolotukhin (Vestnik MGIMO-Universiteta)
The European Free Trade Association (EFTA), established over 60 years ago as an alternative platform for fostering cooperation, has evolved into a crucial component of the pan-European project. The organizational framework underpinning its operations, its developmental trajectory with specific focus on divergences, and the models of differentiated integration (DI) have significantly contributed to its evolution.EFTA's distinct organizational structure, coupled with its pragmatic legal framework, serves as the foundation of its operations. A detailed examination allows for a clear distinction between Switzerland and the three member states of the European Economic Area (EEA), namely Iceland, Liechtenstein, and Norway.Regarding the EEA, its legal framework is established through collaborative development of legal instruments with the EU. The thematic allocation is carefully structured based on existing competencies; officials of EFTA's pillar bodies within the two-pillar EEA structure maintain productive relations with the EU, while others focus on internal matters. The geographical location of these bodies plays a decisive role: Brussels and Luxembourg are aligned with a broad Eurocentric decision-making paradigm, while those within EFTA prioritize endogenous agendas.Switzerland's integration trajectory relies on a diverse array of regulatory mechanisms aimed at bridging disparate areas and fostering cooperation among participating states. A sectoral approach and bilateral agreement packages with the EU are pivotal, with several EFTA bodies operating within Swiss jurisdiction facilitating convergence with the European market. Amidst the current regional turbulence, the convergence of various factors has enabled EFTA to align with the EU's approach to differentiated integration. While earlier scholarly perspectives on the phenomenon were limited in criteria and tools, subsequent empirical developments have provided a more nuanced understanding. The DI models adopted by EFTA member states closely resemble those of the EU, highlighting their alignment. Ultimately, the Association has become an integral part of European integration, with the quartet of participating countries maintaining greater flexibility in decision-making processes.